Uji Kebisingan dan Getaran Mesin Sesuai Regulasi Guna Kenyamanan Kru Kapal - Ary Akbary Musati, Ary Akbary; Prasetyo, Naufal Abdurrahman; Antartika, Meida Perwira (Marine Science and Technology Journal; Vol 5 No 2 (2024): Marine Science and Technology Journal, 2024)
U Noise and vibration tests on ships are important things to pay attention to on ships for crew comfort. If these two things are not paid attention to, it can have an impact on the safety and health of the ship's crew and the construction of the ship itself. This test also aims to determine the human response to vibrations on the ship. This noise and vibration test is carried out during the sea trial process, which is carried out by the classification party. Test case study using TB objects. Marina 2229 which carries out the repair process at the shipyard located in Batam. The purpose of this test is to determine the suitability of the noise test results according to SOLAS 1974 Chapter II-1 part-A and vibration according to ISO 6954: 2000. The test is carried out using qualitative methods, where the results of this test are in the form of numbers, as well as direct observations in the field. The results obtained in all sections are a value interval of 74.1 - 107.1 dB. The noise value does not exceed the permitted SOLAS standard, namely <140 dB. Meanwhile, the vibration test obtained a value range of 0.4 - 3.4. All values obtained still meet ISO standards.